1999
DOI: 10.1542/peds.103.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Newborn and Infant Hearing Loss: Detection and Intervention

Abstract: ABSTRACT. This statement endorses the implementation of universal newborn hearing screening. In addition, the statement reviews the primary objectives, important components, and recommended screening parameters that characterize an effective universal newborn hearing screening program.ABBREVIATIONS. UNHSP, universal newborn hearing screening program; EOAE, evoked otoacoustic emissions; ABR, auditory brainstem response; CDC, Centers for Disease Control and Prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(72 citation statements)
references
References 21 publications
3
64
1
2
Order By: Relevance
“…Thereafter, many studies demonstrated that up to 50% of all newborns with congenital hearing loss do not have any risk factors [7,22] . Hence, UNHS became the accepted strategy for the early identification and intervention of congenital hearing impairment in 1999 [3,11] . In Turkey, UNHS started to be implemented in some pilot hospitals at the end of 2003 [17] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereafter, many studies demonstrated that up to 50% of all newborns with congenital hearing loss do not have any risk factors [7,22] . Hence, UNHS became the accepted strategy for the early identification and intervention of congenital hearing impairment in 1999 [3,11] . In Turkey, UNHS started to be implemented in some pilot hospitals at the end of 2003 [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The test is adversely affected by ear canal debris or middle ear fluid, resulting in referral percentages of 5%-20% when it is performed in the first 24 h of life. The automated ABR test requires newborns to be in a quiet state or asleep at the time of testing, and it may be affected by middle ear fluid or external ear debris as well [3,24] . The referral rates were high in the first step with 31.6% and 28% in the healthy and high-risk newborns, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its use is widely incorporated into universal newborn hearing screening programs and in pediatric clinics where the patients are too young to be cooperative in conventional hearing tests 8 . The OAE technology can have a sensitivity of 95% and specificity of 90% whilst the referral rate is 5-20% when screening is performed within the first 24 hours of life 10 .…”
Section: Newborn Hearing Screeningmentioning
confidence: 99%